Research on Informatization Project Management and Implementation Strategies in the Context of Digital Technology - Liu, Xiangpeng (International Journal of Global Economics and Management, 2023)
With the rapid development of the new generation of information technology, the enterprise’s business model and internal and external environment have undergone a sea change, the traditional information technology project management and implementation mode has been unable to adapt to the rapid innovation of digital technology, to meet the development needs of enterprises, it is necessary to conduct an in-depth study of the enterprise information technology project management and implementation strategy, to explore the new mode of enterprise information technology project management. This paper is mainly from the perspective of information technology project management and implementation of common problems in information technology project management and put forward a series of reflections and suggestions, aimed at providing experience for information technology project management and implementation.